Deposition of Ni-Al coatings by pack cementation and corrosion resistance in high temperature and marine environments. (March 2019) - Kourtidou, Dimitra; Chaliampalias, Dimitrios; Vogiatzis, Christos; Tarani, Evangelia; Kamou, Aikaterini; Pavlidou, Eleni; Skolianos, Stefanos; Chrissafis, Konstantinos; Vourlias, George
Highlights: Al-Ni composite coatings were formed, using electrodeposition and pack aluminizing. A Ni-Fe transition zone was also formed at the substrate-coating interface which is likely to reinforce the adherence. The exposure of the coated samples in high temperature oxidation, favored the creation of more resistant Ni-Al phases. The coating thickness inhibits the evolution of pits when the samples were tested by electrochemical corrosion. The sample pack aluminized at 700 °C for 120 min had the best resistance in high temperature and marine atmospheres. Abstract: Nickel aluminides are ideal materials for protective coatings because they possess high-temperature oxidation resistance and low corrosion rates in marine atmospheres. In this work, a double layered coating was formed by the electrochemical deposition of an initial Ni layer followed by an Al top layer deposited by pack cementation. The coatings were found to contain several Ni-Al on the upper areas and Ni-Fe phases on the substrate/coating interface, as a result of Ni diffusion during the aluminization step. Thermogravimetric high temperature oxidation tests and electrochemical corrosion measurements revealed significant increase of the samples' resistance, compared to the uncoated steel.